(untitled) (Socio-economic relations in the digital society, 2019)
In the current market conditions one of the main problems of the banking system is to create favorable conditions for the continuity of the reproduction process, primarily through timely meet the needs of economic agents. The severity of this problem is that in today’s banking system loans do not fully meet the needs of the economy, is essential shortage of loan capital, because of low income households ineff ective economy, “flight” of capital abroad, the presence of substantial funds out of banks in the shadow economy.Given this updated need to find ways to restore active credit activity of the banking system, which leads to the need for the current state of lending and identifying areas to ensure its dynamics.